An Empirical Calibration for Heat‐Balance Sap‐Flow Sensors in Maize - Wang, Yueyue; Zhang, Xiao; Xiao, Xinhua; Heitman, Joshua; Horton, Robert; Ren, Tusheng (Agronomy journal, 2017)
Core Ideas Sap flow errors with heat‐balance sap‐flow sensors are quantified. An empirical equation is established for correcting heat‐balance sap‐flow measurements in maize. Independent tests proved the usefulness of the calibration equation in maize. Sap flow measurements with heat‐balance sap‐flow (HBSF) sensors are subject to errors due to temperature heterogeneity across the plant stem. Here we develop and evaluate an empirical calibration for HBSF sensors to measure transpiration rates (T) of maize (Zea mays L.). A pot experiment was used to establish an empirical calibration equation relating T determined by a mass balance method and sap flow velocity (V) measured with HBSF sensors. The calibration equation was tested in a field weighing lysimeter study, a pot study from the literature, and an additional dataset where V was measured with HBSF sensors, and T was determined from independent measurements of evapotranspiration and evaporation. In all studies, HBSF sensor measured V overestimated T, and the errors displayed diurnal dynamics: small in the evening and early morning, became larger with increasing T, and reached a maximum when solar irradiance was the largest. A linear calibration equation, T’ = 0.65V + 0.39, was established to convert measured V (g plant−1 h−1) values to corrected transpiration rates T’ (g plant−1 h−1). Using this equation, the largest sap flow error was reduced by 60, 50, and 50% in the lysimeter experiment, pot experiment, and field study, respectively.